Optimization of ultrasonic-assisted extraction of phenolic compounds from Clinacanthus nutans using ionic liquid (ILs) binary solvent: Application of Peleg’s model and response surface methodology - Tong Yen Suan; Saiful Irwan Zubairi; Ruth Naomi Manuel; Zalifah Mohd Kasim; Nur Huda-Faujan (PLoS ONE, 2025)
Clinacanthus nutans (Sabah snake grass) is widely recognized for its pharmacological properties, particularly its high phenolic content and antioxidant activity. However, the optimization of its ultrasonic-assisted extraction (UAE) remains underexplored. This study aims to enhance the extraction efficiency of phenolic compounds from Clinacanthus nutans leaves using ionic liquid (IL) binary solvents, with optimization based on Peleg’s model and Response Surface Methodology (RSM). Peleg’s model was used to determine the optimal extraction time, while RSM with a Central Composite Rotatable Design (CCRD) was applied to evaluate the effects of ultrasonic frequency (40–60 kHz) and the ratio of ILs to water (2:8, 5:5 and 8:2) on total phenolic content (TPC), DPPH radical scavenging activity, and Ferric Reducing Antioxidant Power (FRAP). The experimental results were statistically analyzed using ANOVA, model fitting, and desirability functions. Peleg’s model indicated that the predicted maximum total phenolic content (TPC) of 42.556 ± 0.0003 mg GAE/g was achieved at an ultrasonic frequency of 50 kHz within 3 hours, making this duration as the predictive model benchmark for further optimization. The optimal extraction conditions were identified as an ultrasonic frequency of 60 kHz and an IL-to-water ratio of 2:8, yielding a maximum TPC of 0.01 ± 7.97 x 10−5 mg GAE/g, DPPH antioxidant activity of 95.08 ± 0.57%, and FRAP antioxidant capacity of 6.31 ± 0.10 mg AEAC/g. Peleg’s model inadequately predicted the best exhaustive extraction time prior to RSM leading to a low TPC value throughout the optimization process while maintaining high in antioxidant efficacy. However, the use of IL binary solvents significantly enhanced the release of phenolic compounds compared to conventional solvents, demonstrating their potential as a green extraction alternative. This study highlights the effectiveness of ultrasonic-assisted extraction combined with IL binary solvents for maximizing the recovery of bioactive compounds from Clinacanthus nutans leaves. The optimized extraction method can be beneficial for pharmaceutical, nutraceutical, and functional food industries. Future research should focus on identifying specific phenolic compounds using High-Performance Liquid Chromatography (HPLC), combined kinetic and diffusion equilibrium model and further refining process optimization parameters (e.g., longer concoction duration) to enhance yield efficiency.